SPK Pemberian Pinjaman dalam Upaya Mengantisipasi Kredit Macet pada Anggota Koperasi Studi Kasus: KSP Warna Artha - Imron Imron (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Cooperative Savings and Loans is one type of cooperative in Indonesia that has the main activity is to provide storage services and loan funds to members of the cooperative with the aim of advancing the welfare of members in particular and society in general. From that base, it can be seen that cooperatives contain two elements, namely economic elements and social elements related to each other. It is said to have an economic element because the purpose of the cooperative itself is to achieve the welfare of members. The loan facility in the Artha Color cooperative has a high risk of non-performing loans or bad loans. The incidence of further problem loans may result in difficulties from the cooperative. This study aims to analyze the procedure of granting small and medium business loans and employee loans. The subjects of this research are staff of Artha Color Cooperative employees and members of Artha Color Cooperative. The object of his research is the analysis of the determination of lending employees to members of the cooperative. The data collected by interview method, observation and documentation are then analyzed by Quantitative Descriptive Analysis. The results showed that lending procedures to members of the cooperative has been well implemented starting from the submission of loan demand, analysis of guarantee files, conducting surveys, studying loan files, to disbursement of credit.